2009
DOI: 10.1007/s10661-008-0720-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromium speciation in groundwater of a tannery polluted area of Chennai City, India

Abstract: Chromium speciation in groundwater of a tannery polluted area was investigated for the distribution of chromium species and the influence of redox couples such as Fe(III)/Fe(II) and Mn(IV)/Mn(II). Speciation analysis was carried out by ammonium pyrolidinedithiocarbamate (APDC)-methylisobutylketone (MIBK) procedure. The groundwater samples were analyzed for Cr(III), Cr(VI), and Cr(III)-organic complexes. The APDC could not extract the Cr(III)-organic complexes, but HNO3 digestion of the groundwater samples rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…The investigators determined the dominant pollutant for each site based in part on prior testing or historical use of a site, then took samples to measure levels of the pollutant, typically in only one environmental medium. For sites where only total chromium was reported, the speciation coefficient of 0.6 was used to estimate hexavalent chromium (Avudainayagam et al 2003; Kumar and Riyazuddin 2010). Between 2009 and 2012, investigators completed 1,510 such screenings in 49 countries.…”
Section: Methodsmentioning
confidence: 99%
“…The investigators determined the dominant pollutant for each site based in part on prior testing or historical use of a site, then took samples to measure levels of the pollutant, typically in only one environmental medium. For sites where only total chromium was reported, the speciation coefficient of 0.6 was used to estimate hexavalent chromium (Avudainayagam et al 2003; Kumar and Riyazuddin 2010). Between 2009 and 2012, investigators completed 1,510 such screenings in 49 countries.…”
Section: Methodsmentioning
confidence: 99%
“…Chromium (Cr) is the 7th most abundant metal in the earth's crust and is a hazardous environmental toxicant is released from various industries using Cr [1]. There are several forms of Cr however; trivalent chromium [Cr (III)] and hexavalent chromium [Cr (VI)] are more common in Cr-polluted substrates [2].…”
Section: Introductionmentioning
confidence: 99%
“…In India, numerous sites are contaminated with Cr and the productivity of various crops grown in Cr-contaminated soil may have been adversely effected [1]. This problem further gets exacerbated due the use of Cr-contaminated water by farmers in irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The wide variation in water table is due to the topography of the area. More details on sampling and sample preservation have been reported in a previous paper (Kumar and Riyazuddin 2010). Rainfall data of the area was obtained from State Economics and Statistics Department, Chennai.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Several studies have been reported on simulated systems, but relatively few have been reported on the redox transformations of chromium species in real groundwater environment. In a previous paper, we have reported the speciation of chromium in a contaminated groundwater and the influence of Fe(II), Mn(IV), DO, and redox potential (Eh) on chromium speciation (Kumar and Riyazuddin 2010). Consequently, the study has been continued for a period of 3 years, with the following objectives: (1) to investigate the temporal variation of chromium species and other matrix constituents and (2) to study the redox processes associated with the temporal variation of chromium species.…”
Section: Introductionmentioning
confidence: 99%